Marketing modernism in fin-de-siècle Europe - Jensen, Robert, 1954- (Princeton University Press, 1994)
The commercial success of modernism, argues Robert Jensen, depended greatly on possession of historical legitimacy. The very development of modern art was inseparable from the commercialism many of its proponents sought to transcend. In this fundamental rethinking of the rise of modernism from its beginnings in the Impressionist movement, Jensen explores the economic, aesthetic, institutional, and ideological factors that led to its dominance in the international art world by the early 1900s.